Elicitation of Jerusalem artichoke (Helianthus tuberosus L.) cell suspension culture for enhancement of inulin production and altered degree of polymerisation. (5th April 2016) - Ma, Chunquan; Zhou, Dong; Wang, Haitao; Han, Dongming; Wang, Yang; Yan, Xiufeng
Abstract: BACKGROUND: Plant cell suspension cultures have emerged as a potential source of secondary metabolites for food additives and pharmaceuticals. In this study inulin accumulation and its degree of polymerisation (DP) in the treated cells in the same medium were investigated after treatment with six types of elicitors. RESULTS: An in vitro cell suspension culture of Jerusalem artichoke ( Helianthus tuberosus L.) was optimised by adding an extra nitrogen source. According to the growth kinetics, a maximum biomass of 5.48 g L −1 was obtained from the optimal cell suspension medium consisted of Murashige and Skoog basic medium (MS) + 1.0 mg L −1 α ‐naphthalene acetic acid (NAA) + 1.0 mg L −1 6‐benzylaminopurine (6‐BA) + 0.5 mg L −1 proline + 1.0 mg L −1 glutamine. Methyl jasmonate (MeJA, 250 µmol L −1 ) treatment for 15 days led to the highest levels of inulin (2955.27 ± 9.81 mg L −1 compared to control of 1217.46 ± 0.26 mg L −1 ). The elicited effect of five elicitors to the suspension cells of Jerusalem artichoke is as follows: AgNO3 (Ag, 10 µmol L −1 ), salicylic acid (SA, 75 µmol L −1 ), chitosan (KJT, 40 mg L −1 ), Trichoderma viride (Tv, 90 mg L −1 ), yeast extract (YE, 0.25 mg L −1 ), and the corresponding content of inulin is increased by 2.05‐, 1.93‐, 1.76‐, 1.44‐ and 1.18‐fold compared to control, respectively. The obvious effect on the percentage of lower DP in inulin was observed in cells treated with 40 mg L −1 KJT, 0.25 mg L −1 YE and 10 µmol L −1 Ag. CONCLUSIONS: Among the six types of elicitors, the descending order of inulin content is MeJA > Ag > SA > KJT > Tv > YE. For the purpose inulin with lower DP and its application to prebiotic food, three elicitors, including KJT, YE and Ag, can be used for the elicitation. © 2016 Society of Chemical Industry